2019
DOI: 10.1002/hep.30417
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir and Peginterferon Alfa‐2a in Adults With Hepatitis B e Antigen–Positive Immune‐Tolerant Chronic Hepatitis B Virus Infection

Abstract: Monotherapy with interferon or nucleoside analog is generally not recommended during the immune‐tolerant (IT) phase of chronic hepatitis B virus (HBV) infection. Recognition that high HBV DNA levels are associated with hepatocellular carcinoma has increased interest in treating HBV in the IT phase. Small pediatric studies reported efficacy with combination nucleoside analog and interferon therapy. The aim of this study was to evaluate the safety and efficacy of the combination of entecavir and peginterferon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 25 publications
2
51
2
Order By: Relevance
“…The role of Peg‐IFNα in antiviral therapy in patients with CHB has been an interest of investigators for many years. The benefits of Peg‐IFNα monotherapy in combination with NAs, as well as addition to ongoing NAs, have been reported in different studies; however, these studies have primarily evaluated serological changes …”
Section: Discussionmentioning
confidence: 99%
“…The role of Peg‐IFNα in antiviral therapy in patients with CHB has been an interest of investigators for many years. The benefits of Peg‐IFNα monotherapy in combination with NAs, as well as addition to ongoing NAs, have been reported in different studies; however, these studies have primarily evaluated serological changes …”
Section: Discussionmentioning
confidence: 99%
“…Wu ZX [24] evaluated the efficacy of TDF and LDT combination therapy for chronic hepatitis B patients in IT phase and found that TDF and LDT combination therapy shows a rapid antiviral response in patients with CHB in IT phase. In another ETV and Peg IFN combination therapy study also shows potent antiviral response in patients with CHB in IT phase [17]. However, HBeAg seroconversion rate of patients in these studies was unsatisfactory.…”
Section: Discussionmentioning
confidence: 98%
“…Antiviral therapy with nucleos(t)ide analogues(NAs) can efficaciously inhibit viral replication, relieve liver inflammation, reverse liver fibrosis, reduce HCC incidence and thereby improve the clinical outcomes of patients with chronic HBV infection [10][11][12][13].Therefore, the existing national and international guidelines for the prevention and treatment of chronic hepatitis B (CHB) clearly recommend CHB patients during immune active (IA) phase (HBeAg positive or negative)to undergo antiviral treatment as soon as possible [14][15][16]. However, due to the presence of minimal liver inflammation, no obvious disease activity and poor antiviral efficacy of interferon (IFN) or NAs [17,18], the current mainstream treatment recommendations for CHB patients in immunetolerant (IT) phase are close follow-up until the entry into the IA period [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even if they are included, only 7% of treated patients reached the study endpoints. Feld and colleagues also report their experience in the current issue using a similar regimen in adults with IT chronic HBV . Only 1 (4%) of the 27 patients achieved HBeAg loss, with none experiencing durable HBV DNA suppression ≤1,000 IU off therapy.…”
mentioning
confidence: 99%